Integrating Social Media Strategy with Customer Relationship Management: A Basis for Relationship-Marketing Strategies for Dominican Province of the Philippines Schools - Eunice Mareth Querol Areola, PhD HSG; Jhennie Caldito Villar (Sekolah Tinggi Manajemen IPMI, 2023)
Social Customer Relationship Management (SCRM) is one of the approaches used by companies and service institutions in managing and engaging customer interactions happening on social media. This study attempted to present the significant relationship between SCRM and social media performance of the DPP schools. This paper suggested adopting a relationship-marketing approach, integrating customer relationship management with social media strategy, for educational institutions under the Dominican Province of the Philippines, with the use of the Technology-Organization-Environment model with the diffusion of innovation insights into the relationship marketing. The results showed that there is a significant relationship between SCRM and the social media performance of schools while the respondents are strongly satisfied with the services provided by schools through their respective social media accounts. The research recommends the conduct of SCRM evaluation to validate whether SCRM strategies are aligned with the goals of the institution. Further, future researchers can investigate the 'responsiveness' of schools in terms of SCRM and conduct a study on engaging and impactful content relating to enrollment.